Geographic Distribution Patterns of Soil Microbial Community Assembly Process in Mangrove Constructed Wetlands, Southeast China - Ping Hu; Qiong Yang (Diversity)
Constructed wetlands, as an emerging wastewater treatment system, have been widely used worldwide due to their high purification efficiency and low investment and operating costs. Wetland plants, on the other hand, together with their inter-root microbes, significantly affect the ecological functions of constructed wetlands. The mangrove constructed wetland within Futian District, Shenzhen, China, is a typical wastewater treatment area, but the structure and function of its soil microbial community remain largely unexplored. In this study, the assembly and processes of the soil microbial communities in this constructed wetland were intensively investigated using high-throughput sequencing technology. Our results showed that the three mangrove plants had significant effects on the soil bacterial microbial community α-diversity, insignificant effects on β-diversity, and significant effects on fungal α-diversity and β-diversity. The abundance of genera changed significantly between the treatment groups, such as the genus Candidatus_Udaeobacter for bacteria versus Russula for fungi, and the random forest model showed that rare genera (e.g., Acidibacter, Dyella, Sebacina, and Lachnellula) also play an important role in microbial community construction. Community assembly revealed the deterministic process of soil bacterial and fungal communities under different mangrove species. Overall, this study enhanced our understanding of soil microbial community composition and diversity in constructed wetlands ecosystems, providing insights into their manageability.